EDUCAÇÃO E POLÍTICA EM ROUSSEAU, CAMINHOS PARA A CONSTRUÇÃO DA LIBERDADE: UM ESTUDO SOBRE O SENTIDO POLÍTICO DO PROJETO PEDAGÓGICO DO EMÍLIO DE ROUSSEAU - SILVA, Natal Esteves da (2008)
The social context described in the Discourse on the origin and the bases of inequality between humans corresponds to the thought of Rousseau on the social-politicial aspect of his contemporaneousness. On the other side, the intention of thinker genebrino of having in Emílio a foretelling element of the Social Contract demonstrates clearly his political engagement. This practical preoccupation considers, not only in this work, but, in his theoretical production in general. So, underlying to the emphasis given to the abstract aspects in his politics writings, there is noticed the sketch of a plan of political action. It s on this presupposition that we ask: what it means to form for the citizenship in the social context described in the Second Speech? How does Emílio respond to that? The treatment of this problem of the education of Rousseau presupposes an analytical movement including three mentioned works. What for its time, demands that it has in hands a compatible connecting thread with them. This connecting thread might not be another but the problematic of the freedom. Since it sets itself up as the point of convergence of antropologic, politically and education of Rousseau thought. In the analysis of relation between freedom and human, we saw that it sets itself up as its difference specific, so essential to its existence and what consists of principal attribute of natural human. While leaving the state of nature this freedom is lost, since the social established relations of inconsistent form have a tendency to abolish it. Being the condition of freedom, essential to his existence, there is imposed on a civil human the necessity of rescuing it, now in a compatible format with social life, in other words, what sets a moral or political freedom up. Although freedom is now demanded, one theats of a convention, it s not in human so natural arrangements to his effectuation. Then, it is necessary build them, and this task falls to the education. While moving by Rousseau s theories, indirectly we reaffirm the theory of the unity of his works. And, straightly, we defend the theory of which, the reason of being of Jean-Jacques Rousseau s educational-philosophic work, Emílio or of the education, it is about building necessary arrangements to society according to Social Contract prescriptions.